Electronic Storage Of Notary Protocols Based On A Cloud Computing System In The Cyber Notary Concept - Agung Iriantoro; Banu Sopian Hardiansyah (Jurnal Hukum Prasada, 2024)
The manual storage of notary protocols poses various risks such as damage due to unforeseen events, degradation from chemical influences, destruction by rodents or insects, dispersal, loss, and physical harm. It is crucial for notaries to embrace modern technology for storing notary protocols electronically, particularly through the use of Cloud Computing Systems. According to Article 1 number 13 of the Notary Act, notary protocols are considered state archives that notaries are responsible for preserving in compliance with relevant legal regulations. Therefore, the management of notary protocols should adhere to the Archives Law and Government Regulation Number 28 of 2012. The Notary Protocol, considered a dynamic archive of vital importance, should have the capability to be transformed into electronic documents. As stated in Article 48 and Article 49 paragraph (1) of Government Regulation Number 28 of 2012, the transfer of dynamic archive media is permissible, and such transfer can take any form in line with technological advancements and information regulations. The adoption of a Cloud Computing System for the electronic storage of Notary Protocols reflects the progress in technology and information. The concept of Idea cyber notary involves using technological advancements to enable notaries to perform their notarial responsibilities. Notaries, acting as data controllers and processors for their clients' personal data, have the responsibility to gather, store, and handle such information. In legal terms, notaries can be held accountable for mishandling personal data.